Construction of a C-decorated and Cu-doped (Fe, Cu)S/CuFe2O4 solid solution for photo-Fenton degradation of hydrophobic organic contaminant: Enhanced electron transfer and adsorption capacity. (June 2022) - Xiunan, Cai; Ling, Tian; Meifei, Chen; Yijun, Liu; Wei, Wang; Junhao, Long; Yanjuan, Zhang; Gan, Tao; Huayu, Hu; Zuqiang, Huang
Abstract: To effectively treat the hydrophobic organic contaminant and utilize an industrial solid waste manganese residue (MR), a novel starch-derived carbon (SC)-decorated and Cu-doped (Fe, Cu)S/CuFe2 O4 solid solution (CFS/CFO@SC) was prepared from MR via mechanical activation treatment of precursor materials followed by one-step pyrolysis and applied as a photo-Fenton catalyst to treat a hydrophobic organic compound, 17α-ethinylestradiol (EE2). Characterization results showed that the CFS/CFO@SC solid solution with unique crystal and electronic structures exhibited high adsorption capacity and catalytic activity, ascribed to that Cu doping and C decorating enhanced its hydrophobicity and BET surface area. The CFS/CFO@SC showed excellent degradation efficiency with nearly 100% of EE2 removal rate in 40 min (degradation rate constant of 0.112 min −1 ), and a high mineralization degree with 95.2% of TOC removal in 180 min. This could be ascribed to that C decorating and the formation of CFS/CFO solid solution promoted the charge transfer in a continuous band, resulting in effective separation of photogenerated holes–electrons (h + –e – ). The strong interaction of Fe–Cu collaborating with the photoelectron could effectively accelerate the recycle of Fe 3+ /Fe 2+ and Cu 2+ /Cu +, thus generating more active radicals. Moreover, CFS/CFO@SC showed promising stability and recyclability with the EE2 removal rates all >95% after five cycles. This work brings a valuable approach for the rational design of high-performance Fe-based photo-Fenton catalysts for environmental remediation and the valorization of MR. Graphical abstract: Image 1 Highlights: A new Fe-based solid solution with high photo-Fenton catalytic activity was prepared. C decorating greatly enhanced the hydrophobicity and BET surface area. Formation of C-decorated and Cu-doped solid solution boosted charge transfer. Effective degradation of hydrophobic contaminant catalyzed by the solid solution. The mechanism based on adsorption and catalytic degradation was proposed.